In vitro probiotic properties of enterocin-producing Enterococcus mundtii and Enterococcus faecium strains isolated from sheep and goat colostrum - Öztürk, H; Geniş, B; Özden Tuncer, B; Tuncer, Y (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of this study was to investigate the in vitro probiotic properties of enterocin-producing 11 E. mundtii and two E. faecium strains previously isolated from sheep and goat colostrum. It was determined that only E. mundtii HC26.1, HC56.3, HC73.1, HC73.2, HC147.1, and HC166.5 survived after 3 hours at pH 3. Survival rates of E. mundtii HC26.1, HC56.3, HC73.1, HC73.2, HC147.1, and HC166.5 strains were calculated as 27.98%, 27.43%, 29.16%, 25.89%, 25.66%, and 29.61%, respectively. However, none of them survived in artificial gastric juice. The survival rates of Enterococcus strains in MRS broth containing 0.3%, 0.5%, and 1% bile salt were found to be at least 47.42±0.74%, 41.63±1.41%, and 17.15±0.00% after 24 hours, respectively. It was determined that all of the strains were grown in a medium containing lysozyme and tolerated the presence of phenol. All of the strains showed taurodeoxylic acid and glycodeoxycholic acid (except for E. faecium HC161.1) hydrolase activities. All strains except E. faecium HC161.1 showed over 40% hydrophobicity. After 24 hours, the autoaggregation and coaggregation values of the strains were found to be between 34.33-49.17% and 24.78-46.47%, respectively. As a result of the study's findings, it is believed that Enterococcus strains might be employed as probiotic cultures if microencapsulation increases their resistance to the harsh conditions of the stomach.